Carcinoid tumor of the jejunum: (alteration of the superior mesenteric vessels) - Davidenko, Nicolás; Casanova, Marys; Silva García, Ernesto; Zito, Milton; Estrugo, Roberto; de Stefani, Eduardo (Cirugía del Uruguay, 1973)
A patient had a carcinoid jejunal tumor, diagnosed with the aid or pathological anatomy, and considerable mesenteris metastasis displacer towards the large vessels. Oleohepatography and arteriography showed hepatic metastasis, but not gammagram, Mesenteric vessels had aJtered and superior mesenteric arteriography indicated discreet initial dilatation, reduced calibre and terminal stenosis; there was reducton of blood flow towards periphery. Si1ce worldwide experience on the subject is limited we believe that this contribution is of value with respect to vascular pathology of this tumor.